The modification of electrodes with poly(4-vinyl-4′,4″-dibromotriphenylamine) - Compton, R; Day, M; Ledwith, A; Abuabdoun, I (1986)
The synthesis of the novel polymer poly(4-vinyl-4′,4″- dibromotriphenylamine) is described along with the properties of modified electrodes based on this polymer which are shown to mediate the oxidation of carboxylate anions.